Pengaruh Metode VAKT terhadap Kemampuan Mengenal Bangun Datar pada Siswa Disabilitas Intelektual Sedang Kelas III - Sulasmi, Tri; Prystiananta, Nostalgianti Citra; Sugihartatik, Sugihartatik (JOEAI (Journal of Education and Instruction), 2025)
This study aims to investigate the impact of the VAKT method on students with moderate intellectual disabilities' ability to recognize plane figures. The research method employed was an experimental design, specifically Single Subject Research (SSR). This study design consisted of two phases: an A-B design, where Phase A served as the baseline and Phase B served as the intervention. Data were collected during the baseline phase, which was an observational phase where students assessed their initial abilities with plane figures. The intervention phase, which followed the observation phase after the students received treatment (intervention), consisted of five sessions in the baseline phase and ten sessions in the intervention phase. Based on the study's results, a student with a moderate intellectual disability, identified as A, in grade III at SLB C TPA Jember, consistently improved during the intervention phase, reaching a maximum score in the final three sessions. The average score percentage in the baseline phase was 43.75%, while in the intervention phase it increased to 89.84%. The conclusion is that the application of the VAKT method (Visual, Auditory, Kinesthetic, and Tactile) has proven effective in improving the ability to recognize plane figures.   Keywords: Understanding Planar Shapes, VAKT Method, Students with Moderate Intellectual Disabilities